Continuous Consumption of Reused Palm Oil Induced Hepatic Injury, Depletion of Glutathione Stores, and Modulation of Cytochrome P450 Profiles in Mice - Waranya Chatuphonprasert; Yollada Sriset; Kanokwan Jarukamjorn (Polish Journal of Food and Nutrition Sciences)
Cooking oil deteriorates with repeated thermal exposure, resulting in appearance change and formation of oxygen radicals. Consumption of the deteriorated oil causes oxidative stress related to lipid metabolism. This study evaluated the effects of palm ( Elaeis guineensis Jacq.) oil on hepatic histology, redox status, and cytochrome P450 (CYP) profiles. Adult female mice were orally given purified water (control), fresh, or reused palm oil (4.5 g/kg/day) daily for 16, 24, and 36 weeks. The livers were then collected for histological examination and for the evaluation of the redox system and CYP expression profiles. Treatment with fresh oil for 36 weeks resulted in some pyknosis and karyorrhexis in hepatic tissues, while reused oil resulted in more injuries to the nuclei with hepatic fat accumulation from week 24 onwards. Depletion in reduced glutathione (GSH) stores, with a significant decrease in the GSH/GSSG ratio, was observed with the reused oil but not with the fresh oil. The expression profiles of drug-metabolizing CYPs were significantly modulated; Cyp2c29, Cyp3a11 , and Cyp3a13 were suppressed by both fresh and reused oil, while only the reused oil elevated Cyp2e1 . The expression of Cyp4a10 and Cyp4a14 , the key enzymes in lipid metabolism, were expectedly up-regulated by both. These findings suggest reused oil has a deleterious effect on hepatic ultrastructure, induces an imbalance of redox state, and causes Cyp2e1 activation-associated oxidative stress. It is therefore recommended that fresh rather than reused palm oil be used for cooking, and large-scale or long-term consumption be avoided to reduce the risk of liver damage and drug-interactions.